By-product manufacturing from rice industry waste materials: a review / Zulaikha Othman - Othman, Zulaikha (Faculty of Plantation and Agrotechnology, 2017)
Rice is an important staple food for almost half of the world population. High demand of rice will increase more rice residue left in the field after rice is harvested. The amount of by-product rice cultivation such as rice straw, rice husk, rice husk ash and rice branare grow each year is roughly equal to the amount of rice production. Open-field burning can reduce rice waste abundance, however it cause pollution and not environmental friendly. This paper is to review the component in the rice by-product, as well as the benefits in different industries that associated with these by-products. Due to rapid growth in population and industrialization, various new technologies are made to reduce the waste in industrial processing. From this rice by-product, it can be converted into a value-added products that can be used in different industries such as agricultural, bioenergy, pharmaceutical, construction, foods and cosmetics industrials.